Modelling Fractal Waves on Shallow Water Surfaces via Local Fractional Korteweg-de Vries Equation - Xiao-Jun Yang; Jordan Hristov; H. M. Srivastava; Bashir Ahmad (Abstract and Applied Analysis)
A mathematical model of fractal waves on shallow water surfaces is developed by using the concepts of local fractional calculus. The derivations of linear and nonlinear local fractional versions of the Korteweg-de Vries equation describing fractal waves on shallow water surfaces are obtained.